Recent Progress in Quantitatively Monitoring Vesicular Neurotransmitter Release and Storage With Micro/Nanoelectrodes - Liu, Yuying; Du, Jinchang; Wang, Mengying; Zhang, Jing; Liu, Chunlan; Li, Xianchan (Frontiers in Chemistry, 2021)
Exocytosis is one of the essential steps for chemical signal transmission between neurons. In this process, vesicle docks and fuses with the plasma membrane and release the stored neurotransmitters through exocytotic pore into the extracellular space, and all of these steps are governed with various molecules, such as proteins, ions and even lipids. Quantitatively monitoring vesicular neurotransmitter release in exocytosis and initial neurotransmitter storage in individual vesicles are significant for the study of chemical signal transmission of central nervous system (CNS) and neurological diseases. Electrochemistry with micro/nano-electrodes exhibits great spatial-temporal resolution and high sensitivity. It can be used to examine the exocytotic kinetics from the aspect of neurotransmitter and quantify the neurotransmitter storage in individual vesicles. In this review, we first introduce the recent advances of single cell amperometry (SCA) and the nanoscale interface between two immiscible electrolyte solutions (ITIES), which can monitor the concentration and release kinetics of electrochemical and non-electrochemical active neurotransmitters, respectively. Then, the application of the vesicle impact electrochemical cytometry (VIEC), intracellular vesicle impact electrochemical cytometry (IVIEC), and their combination with other advanced techniques can further explain the mechanism of neurotransmitter storage in vesicles before exocytosis. It has been proved that these electrochemical techniques have great potential in the field of neuroscience.